Accounting in the Cloud - Sutthikun, Wiranya; Thapo, Rati; Sahayrak, Kongkia (International Journal of Integrated Education and Development, 2018)
In the current financial crisis and being challenged by the impact of globalization, the wide spread of internet-based application, the world has come to rely on technology. A new concept of cloud accounting has become as a revolution to information technology (IT) provision, management and security. In this article authors focuses on the impact of cloud computing, benefits and challenges of the software and comparison on traditional accounting software vs cloud accounting software.